The Relationship between Employees’Well-Being and Economic Performance in Serbia - Kontic, Ljiljana; Bracun, Erika (Journal of Behavioral Economics and Policy, 2025)
The importance of employees’ well-being has grown because it affects productivity, satisfaction, mental health,company reputation, and legislation in developed economies. Previous studies show that psychological safety is vital for innovative decision-making and entrepreneurial behavior. This paper investigates the relationship between employees’ well-being and economic performance in a transition economy. Serbia serves as a case study. The sample included 3050 employees from 100 Serbian companies across all industries. The research used a mixed-method approach. Quantitative data were analyzed with statistical methods. In-depth insights were gained through semi-structured interviews with 75 Human Resource managers. The results reveal that psychological safety and engagement affected profitability, productivity, retention, and innovation output. Absenteeism was higher when stress levels were higher. They reduce profitability and productivity by draining focus and motivation. Work-life balance improves economic performance by increasing satisfaction and reducing turnover. By recognizing psychological safety, stress, and work-life balance as key factors, this study sheds light on behavioral economics in a transition environment. These psychological mechanisms—empowering safe risk-taking, managing stressors, and supporting work-life balance—are critical determinants of economic outcomes at multiple levels. In Serbia’s changing market, investing in employees’ well-being should be seen as a way to improve social welfare. Maintaining progress and adjusting to an increasingly complex organizational landscape requires ongoing research and innovative policy. Policy recommendations aimed at fostering this psychological mechanism will be discussed to inform strategic initiatives.